SURGICAL TREATMENT OF ANAEROBIC DEEP NECK INFECTION COMPLICATED BY MEDIASTINITIS - E. V. Lishov; A. A. Kharitonov; A. M. Putintsev (Acta Biomedica Scientifica)
The article analyzes the surgical treatment of 78 patients with deep neck total necrotic phlegmon. It was revealed that in 95 % of cases in the early period are complicated by descending mediastinitis. The pre-examination stage included: X-ray of the neck by Zemtsov and chest X-ray, ultrasound examination of pleural cavities, thoracic and mediastinal MSCT The surgical stage included opening and draining of the abscess, revision of the deep cellular spaces of the neck and upper mediastinum. In 65 (83.3 %) case thoracomediastinoscopy and decompressive mediastinotomy were performed. In 58 patients, "programmed" bilateral thoracoscopic sanations were performed, with drainage of the mediastinum. Anaerobic microflora made 84.6 % of the infection. The total necrotic phlegmon of the deep cell spaces of the neck in 95 % is complicated by descending necrotizing mediastinitis. Local signs of inflammation, with necrotic phlegmons of the neck, do not allow to determine involvement in the inflammatory-destructive process of mediastinum. The absence of early findings from radiological exam does not exclude the presence of descending necrotizing mediastinitis. Autopsy and revision of the deep cellular spaces of the neck in 87.8 % does not eliminate the spread of the necrotic process along the mediastinal fiber. Active surgical tactics in the total phlegmon of the deep cellular spaces of the neck is justified and allows us to recommend one-stage drainage on the neck and thoracic-mediastinal sanation.